Trading-Off National and Supranational Collective Goods: The Birth and Death of Neoliberal Pluralism. Issue 4 (1st October 2016) - Masini, Fabio
Abstract: The division of power among different layers of government and the designing of international institutions are crucial for the neoliberal project. Nevertheless, this can be approached in two very different ways. The first is to limit the power of national bodies to provide collective goods, the core of the welfare state, through supranational rules and agencies, oriented to provide only a market-preserving framework. The second is to assign powers to different layers of government following issues of efficacy and effectiveness of public intervention. The former is the approach to supranational federalism that proved successful in the last few decades. We explore its evolution and show that the neoliberal thought collective, in its origins, had a much more heterogeneous and pluralistic attitude toward the trade-off between national and supranational public goods.